Exploring AI-Driven Public Services in Semarang : E-Governance and Economic Development Study - Hanifa Maylasari; Nilam Adini Rakhma (Universitas Tidar, 2025)
The rapid growth of information technology has led to advancements in government administration through e-governance, which provides digital, and the private sector. This study objective examines the role of the Semarang City Government in utilizing e-governance technology with artificial intelligence (AI) and its impact on regional economic conditions. Drawing on the framework of the public sphere and deliberative democracy, particularly Jurgen Habermas' concepts, this study investigates the performance of AI-based e-governance services in Semarang City in relation to the economy. The study hypothesizes that the e-governance service system represents a new paradigm and is subject to institutional constraints. The applications used in the e-governance system carry the meaning of e-government. In response, the involvement of the private sector in cooperation, contribution, and economic drivers has a conservative logic. The method used in this research are document analysis and comparison. The findings reveal that AI-based e-governance services influence the economic stability of a region, primarily in the percentage of poverty alleviation. Artificial Intelligence in services effecrively offers economic improvement through strategic measures. The findings in this chapter offer refelections on the progress of service technology in Semarang City, enabling it to promote fair and inclusive public welfare.